Outcome of distal clavicular fracture treated conservatively - Abot, Muhammad Syukree; Mohd Yusof, Nazri (IIUM Press, International Islamic University Malaysia, 2017)
Distal clavicle fractures account for 10 to 15% of all clavicle fractures. Traditional management of displaced distal clavicle fractures has been with internal fixation. Several authors have reported higher rates of non-union and poor outcome in conservatively managed fractures. However, long term follow up of non-operated distal clavicle fractures has shown comparable functional outcomes to those managed with internal fixation. This is a cross sectional study of forty one patient with closed fracture distal of clavicle evaluating the functional and clinical outcome of patient following fracture of distal clavicle treated conservatively who has completed six month of treatment in Hospital Sultan Ismail, Johor Bahru. The patient self-evaluation outcome was determined by the presence of one or more affirmative answers on the Simple Shoulder Test. The functional outcome was assessed based on shoulder abduction strength, range of motion of shoulder. This functional outcome was measure using Constant Score consisting of four variables that assess shoulder function, based on the guidelines of the European Society for Shoulder and Elbow Surgery (ESSES). This study showed that distal clavicle fracture treated conservatively has an overall fair functional outcome with mean value of 67.98. Patient with non-union has more pain and has lower level of comfortable hand function. Poorer functional score were observed in patient with tenderness at fracture site after treatment regardless of union or non-union. Patient age, type of fracture and involvement of either dominant or non-dominant limb has no correlation toward the functional outcome.